Miscibility of PEO-b-PCL and its Component Polymers with PVPh at the Air/Water Interface - Pan, Hui-Ting; Hsu, Wen-Ping (Journal of Composites and Biodegradable Polymers, 2019)
The mixed monolayer behavior of polyethylene-block-polycaprolactone (PEO-b-PCL) and its component polymers (PEO or PCL) with poly(vinyl phenol)(PVPh) was investigated from the measurements of surface pressure-area per molecule (π-A) isotherms at three different temperatures(10˚C, 25˚C and 40˚C). The miscibility and nonideality of the mixed monolayers were examined by calculating the excess surface area as a function of composition. Interestingly, PEO and PCL were shown to have different interactions with PVPh at the air/water interface from in the bulk state on the solid substrate. PE O demonstrated mostly positive excess surface area with PVPh. Negative excess surface areas were in the majority observed in the PCL/PVPh monolayers. A scheme of differences in interaction sites between PEO (or PCL) and PVPh at the air/water interface was proposed to explain the negative or positive deviations of surface areas successfully.